2017
DOI: 10.1097/md.0000000000006502
|View full text |Cite
|
Sign up to set email alerts
|

Urethral hemangioma in a prepubertal female patient

Abstract: Rationale:Urethral hemangiomas commonly occur in men or elderly women. We presented a rare case of urethral hemangioma in a prepubertal female patient.Patients concerns:An 8-year-old girl had the complaints of bloody staining of clothing, a foul perineal odor, and urethral pain. She was brought to our genitourinary outpatient department for survey and a single, 1-cm compressible reddish nodule at the 10-2 o’clock position in the distal urethra was found.Diagnoses:Urethral hemangioma in a prepubertal girl was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Li et al reported the youngest case of urethral hemangioma in an 8‐year‐old girl . That reported patient and our patient had similar complaints such as bloody staining of clothing and a foul perineal odor.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Li et al reported the youngest case of urethral hemangioma in an 8‐year‐old girl . That reported patient and our patient had similar complaints such as bloody staining of clothing and a foul perineal odor.…”
supporting
confidence: 77%
“…Prostatic, bladder, urethral, and perineal hemangiomas have been reported only rarely. To our knowledge, although urethral localization of hemangioma is reported in a few boys, only one girl has been reported in the literature to date …”
mentioning
confidence: 95%